Standard abbreviations in students' translations from English into Serbian - Gavranović Valentina M.; Čorboloković Saša S. (Zbornik radova (Univerzitet u Kragujevcu. Pedagoški fakultet u Užicu))
This paper investigates abbreviations that are commonly used in writing in the Serbian and English languages with the aim of examining how well students know and apply abbreviating rules when translating from English into Serbian. It focuses on orthographic rules pertaining to writing abbreviations, the most common mistakes, and the analysis of whether these mistakes result from different orthographic solutions in both languages, linguistic interference, or the creation of a pseudo-norm. The instrument used in this research relied on a test with 20 sentences in English that contained the keywords in their full and abbreviated form in parentheses. The aimed words were given in contextualized sentences so that the students could better understand their meaning and form. The abbreviations were classified and analyzed according to the origin and method of shortening, as defined in Pravopis srpskoga jezika. Both qualitative and quantitative methods were used in the research. The analysis of the results shows that there are subtle similarities and differences between the Serbian and English languages when writing down abbreviations, and many rules that overlap. The main conclusions obtained from the analysis of students' results point to the following: students scored the highest results when applying abbreviating rules to writing general (domestic) abbreviations, especially those that have long been part of our orthographic practice, while the lowest scores can be observed when abbreviating acronyms. By comparing English and Serbian orthographic rules, the mistakes can be interpreted by the influence of the English language (punctuation, capital letters), the length of use of certain abbreviations in Serbian orthography (some newer abbreviations have not yet been established), and the absence of certain extra-linguistic knowledge. The results also show the need to pay special attention to the writing of foreign abbreviations in the Cyrillic alphabet, as well as to those abbreviations of foreign origin that are often misspelled due to the lack of proper understanding. The implication of this study relates to a need to create a teaching and learning framework that focuses on the similarities and differences between the two languages, by contrasting examples in context, so that students can better understand the nature of this orthographic aspect.